Comparative tests of bamboo with other woods for structural purposes - Manalo, Vicente G.; Moffatt, George A. (My University, 1908)
Introduction: The apparatus used during the test was a “Riecle” Testing Machine of 100,000 lbs. capacity and located at the Engineering Laboratory, Kansas State Agricultural College. In general the machine is classified into the following parts. 1. The Straining Mechanism. 2. The Weighing Apparatus. 3. The Screw and Vernier Beams. 4. The Driving Mechanism.
Citation: Manalo, Vicente G. and Moffatt, George A. Comparative tests of bamboo with other woods for structural purposes. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Bamboo; Wood; Engineering; Graduating theses; Senior theses; Theses